Las experiencias límite del tiempo en Querido primer novio de Zoé Valdés - Torijano Navarrete, Olivia (Verba hispanica, 2013)
Zoé Valdés, a Cuban writer currently living in exile in France, wrote Dear First Love, a story narrated by multiple narrator-characters, including Time itself. In this book, the time in which the characters and objects exist is transient, however, it is possible to determine the moment of enunciation and in this way discover that the story is a myth created within that fiction. This emerges from the discordancy between actual time and mythical time, a subject much discussed by Paul Ricoeur. The protagonist of the novel travels backin time by means of her memory, while at the same time goes on an actual journey to rescue the beloved of his memories. Such limit-experiences are associated with the axial moment, since without the latter it is not possible to understand the chronological succession of events: one cannot tell what came first or what comes next. Limit-experiences occur when monumental time in the novel coincides with the chronological time of the characters. When trying to explain this situation, it becomes clear that the character develops his orher life and actions at their own pace within their world, and thus time may have a different meaning for each of the characters.
Keywords: Valdés, Zoé, 1959-; Valdés, Zoé: Querido primer novio; kubanska književnost; čas; literarne študije